Pengembangan Model Pembelajaran Use Pre-Test Based Learning (UPBL) Untuk Meningkatkan Kemampuan Kognitif Pada Pelajaran Mikrobiologi Kesehatan Siswa SMK Kesehatan Bina Karya Medika Ponorogo - Susiani, Ely Tri; Isnawati, Isnawati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The use Pre-Test Based Learning (UPBL) model is a development model of the Problem Based Learning (PBL) model that has long been used in learning. The results of the preliminary study of the implementation of Problem Based Learning (PBL) there are some students who are not complete in learning. Based on this, the researcher tried a new model, namely Use Pre-Test Based Learning (UPBL). This study aims to test the effectiveness of the Use Pre-Test Based Learning (UPBL) model to improve cognitive abilities in health microbiology lessons for health vocational students. The method in this research is Research and Development (R&D) from Sukmadinata with 3, steps 1) preliminary study; 2) model development; and 3) model testing. The results showed that the Use PreTest Based Learning (UPBL) model was effective for improving the cognitive abilities of health vocational students in health microbiology lessons.